Modelling uncapacitated facility location problem with uncertain customers’ positions - Huang, Xiaoxia; Di, Hao (Journal of intelligent & fuzzy systems, 2015)
Abstract This paper discusses an uncapacitated facility location problem with customers’ positions subject to experts’ estimations. Uncertain variables are used to describe the estimations of customers’ positions, and an expected distance minimization model is proposed. In addition, a hybrid intelligent algorithm for solving the proposed model problem is provided. To illustrate the application of the new model and show the effectiveness of the solution algorithm, a numerical example is also presented.